Current Emotion Research in Economics - Klaus Wälde; Agnes Moors (Institute for the Study of Labor (IZA), 2016)
Positive and negative feelings were central to the development of economics, especially in utility theory in classical economics. While neoclassical utility theory ignored feelings, behavioral economics more recently reintroduced feelings in utility theory. Beyond feelings, economic theorists use full-fledged specific emotions to explain behavior that otherwise could not be understood or they study emotions out of interest for the emotion itself. While some analyses display a strong overlap between psychological thinking and economic modelling, in most cases there is still a large gap between economic and psychological approaches to emotion research. Ways how to reduce this gap are discussed.
Keywords: A12; B0; D03; 330; emotions; decision making; theory